Barriers to gender equity for female healthcare academicians and researchers in Pakistan: Is it still an issue? - Malik, Madeeha; Hussain, Azhar; Hashmi, Ayisha; Saeed, Hamza; Azhar, Hafsa; Abbasi, Aqsa Sajjid (Frontiers in Public Health, 2023)
Introduction Gender inequity in healthcare academia is rising. Female healthcare professionals are struggling to balance their work and family leading to reduced productivity and disparity in three main areas of academic evaluation including teaching, service and research. Objective The objective of the current study was to explore perceptions of healthcare academicians regarding gender equity and its associated barriers in healthcare academia in Pakistan. Methodology A qualitative study design was used. Study site for this research included medical colleges, pharmacy schools and healthcare educational institutes. Study respondents included healthcare professionals including doctors and pharmacists working as faculty members. Snow ball sampling was used and interviews were conducted till saturation point was achieved. All interviews recorded were transcribed verbatim. Transcribed interviews were then subject to thematic analysis and were analyzed for relevant content. Results Thematic analysis of the study yielded many themes and sub themes. The main themes include: Gender equity an issue for healthcare academicians; Barriers toward promoting gender equity among healthcare academicians; Perceived teaching effectiveness among female healthcare academicians; Professional relationship of female healthcare academicians; Representation of female healthcare academicians at leadership positions; Research opportunities for female healthcare academicians; impact of academia as profession on married life and Strategies for improving gender equity disparities in academia of healthcare profession. The results showed that almost all the females as well as male healthcare academicians were of the view that female academicians are competent, hardworking and committed with their jobs. Mixed responses were observed regarding teaching effectiveness of female academicians. Half of the females as well male healthcare academicians thought that female were more effective teachers while other half was of the view that teaching effectiveness is based on individual trait irrespective of gender. Conclusion The results of the present study concluded that majority of the male as well as female healthcare professionals perceived gender equity as an issue in academia in Pakistan, especially in underprivileged areas. Non-conducive work environment, harassment at workplace and cultural issues were the main barriers identified toward gender equity in healthcare academia in Pakistan.